2021
DOI: 10.1016/j.msard.2021.102906
|View full text |Cite
|
Sign up to set email alerts
|

Rabies vaccination and multiple sclerosis relapse: A retrospective cohort study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Fifteen studies met the eligibility criteria, 1 of them investigated the risk of MS exacerbation following any vaccination, 17 and 14 studies addressed safety concerns related to individual vaccines (hepatitis B, tetanus, influenza, BCG, varicella, tick-borne encephalitis (TBE), rabies, and yellow fever). [18][19][20][21][22][23][24][25][26][27][28][29][30][31] Evidence on the safety of TBE, rabies, and yellow fever vaccination will be reviewed in Question 7. Details on the methodology, level of the evidence and results of the included studies are available in Supplemental Appendix 3.…”
Section: Results and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen studies met the eligibility criteria, 1 of them investigated the risk of MS exacerbation following any vaccination, 17 and 14 studies addressed safety concerns related to individual vaccines (hepatitis B, tetanus, influenza, BCG, varicella, tick-borne encephalitis (TBE), rabies, and yellow fever). [18][19][20][21][22][23][24][25][26][27][28][29][30][31] Evidence on the safety of TBE, rabies, and yellow fever vaccination will be reviewed in Question 7. Details on the methodology, level of the evidence and results of the included studies are available in Supplemental Appendix 3.…”
Section: Results and Recommendationsmentioning
confidence: 99%
“…6 Six studies have evaluated the efficacy and/or safety of travel vaccines in pwMS. [26][27][28][29][30][31] Details on the methodology, level of the evidence, and results of these studies are available in Supplemental Appendix 3.…”
Section: Vaccination In Elderly Pwmsmentioning
confidence: 99%
“…Rabies . A single self‐controlled retrospective study ( Level 3 ) reported the risk of relapses in 55 patients with MS who underwent pre‐exposure rabies vaccination [26]. The annualized relapse rate in the pre‐exposure, exposure risk and post‐risk periods were 0.44, 0.22, and 0.10, respectively (rate ratio for exposure‐risk to pre‐exposure periods, 0.51 [95% CI 0.10–1.68]).…”
Section: Results and Recommendationsmentioning
confidence: 99%
“…Fifteen studies met the eligibility criteria, one of which investigated the risk of MS exacerbation following any vaccination [17], and 14 of which addressed safety concerns related to individual vaccines (hepatitis B, tetanus, influenza, BCG, varicella, tick-borne encephalitis [TBE], rabies, and yellow fever) [18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Evidence on the safety of TBE, rabies, and yellow fever vaccination will be reviewed in Question 7.…”
Section: Safety and Efficacy Of Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation